Resilience of Nematode Connectomes Based on Network Dimension-reduced Method - Dongli, Duan; Xixi, Wu; Shubin, Si (Frontiers in Physics, 2021)
The whole map of nematode connectomes provides important structural data for exploring the behavioral mechanism of nematodes, but to further revel the evolution mechanism and resilience pattern of nematode neurons, it is necessary to effectively couple the regulatory relationship between neurons and their topology. Here, with a typical signal excitation function we propose a model to captures the interacting relationship between the neurons , which actually are high dimensional differential equations. With mean-field theory, we decouple this N-dimension question into a one-dimension problem mathematically. With our framework, we emphatically analyze the characteristics, similarities and differences of the structure and dynamical behaviors of the neuronal system for Caenorhabditis elegans and Pristionchus pacificus. The comparing results of simulating method and theoretical approach show that the most important homologous synapses between C.elegans and P. pacificus are I2 and NSM, which may lead to their different behavior characteristics of predation and prey. The dynamical behaviors present that M4 synapse would degenerate in P. pacificus, but may evolve in C.elegans. Furthermore, in the hermaphroditic and male C. elegans, we test the control level of the intermediate neuron groups over the output neuron groups and the single neuron. The gained insights can be utilized to extract meaningful information about the controlling mechanism between nematode neurons and the resilience of the neuron networks, potentially enabling focused research on the interacting relationship and its interpretation mechanism for artificial neural networks.